Media Sebagai Wadah Pelestarian Budaya Jawa - Pramana, Pramana; Priastuty, Chairunnisa Widya (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2023)
Indonesia is a culturally diverse country. Java is a tribe with a plethora of cultural endowments. Cuisine; music; dance; rituals/ceremonies; craft; calendar (calendar); language; to architecture or buildings that exist in Javanese cultural traditions are examples of Javanese cultural assets. Javanese culture is an essential element in Indonesia's variety that other countries do not own. As a result, it is critical to maintain Javanese culture as one of Indonesia's original resources. However, in the contemporary period, the people began to believe that Javanese culture, as the original traditional culture of Indonesia, was antiquated and out of date. The advancement of information and communication technology in the modern period can be viewed from two perspectives: positive and harmful. This paper is the end outcome of qualitative study. The documentation study method, one of the qualitative data collecting methods used in this writing, is used to collect data in this writing by reading and analyzing associated documents. Denis McQuail's media theory as part of mass communication is used as the analysis knife in this work. As a result, with correct management, the media can be used to preserve Javanese culture. Not only can the media educate, but it may also serve as a marketing vehicle for Javanese culture, resulting in economic rewards.